2022
DOI: 10.1177/10499091221098664
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Toward Hospice and Palliative Care: Instrument Validation Among Emergency Providers

Abstract: Background: Emergency providers can engage in goals of care discussions and hospice and palliative care referrals. Little is known about their knowledge and attitudes, which may influence these care practices. Objective: This study aims to re-validate the knowledge and attitude towards hospice and palliative care (KAHP) scale and assess the scale’s latent constructs among emergency providers. Methods: The scale consists of ten items measured on a five-point Likert scale. Five of the ten items were reverse scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Poor knowledge scores were associated with inadequate PC training and limited available guidelines for practice. 17 , 18 , 19 Interestingly, we found no consistent improvement in knowledge as level of training in emergency care progressed. Scores did not appear to differ between subjects who had received some training versus those who had not, those with a basic medical degree and those with a DipPEC or between registrars and medical officers.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Poor knowledge scores were associated with inadequate PC training and limited available guidelines for practice. 17 , 18 , 19 Interestingly, we found no consistent improvement in knowledge as level of training in emergency care progressed. Scores did not appear to differ between subjects who had received some training versus those who had not, those with a basic medical degree and those with a DipPEC or between registrars and medical officers.…”
Section: Discussioncontrasting
confidence: 56%
“…This may be because ED doctors are experienced in the use of potent analgesics, such as the opioids. 24 As reported in other studies, 17 , 18 however, we noticed weaknesses in knowledge of the management of other physical symptoms and of psychological issues.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Considering that the population classified as having serious life-limiting illnesses had an estimated six months or less to live, it is debatable if such ICU admission these older adults experienced were of any benefit. While physician characteristics and local practice patterns may influence the decision to provide intense care to patients with serious life-limiting illnesses, [30][31][32][33][34] patients and family determinants equally exist. Earlier studies have reported that physicians' race/ethnicity, years of practice, and attitudes toward end-of-life care influence the decision to provide life-prolonging treatments for dying patients.…”
Section: Discussionmentioning
confidence: 99%